Estudo da aplicação dos processos Fenton e foto-Fenton no tratamento de águas contaminadas por diesel/biodiesel - Teofani Koslides Mitre (2012)
The research investigated the oxidative decomposition of diesel and biodiesel blends in water using the photo-Fenton process, as was also evaluated their aerobic degradability by Zahn-Wellens method. Over the 28 days of testing, the biodegradability of the diesel did not change by small biodiesel additions, which was verified by similar degradation values for B0 (0% biodiesel) and B5 (5% biodiesel). The change of biodegradability of the mixtures was only significant from the B75 (75% biodiesel), where there was a removal of 80% of organic matter at 28 days. Before being conducted oxidation testing of the mixture of fuel by chemical processes, carried out a study of Factorial Experiment Design and Response Surface Methodology for B0 and B100 (100% biodiesel) to check the best operating conditions for the processes. It was found that B100 is easily oxidized while B0 is resistant to oxidation. A second-order polynomial response equation was best related dependent variables, [H2O2] and [Fe2+] for Fenton e [H2O2]:COD and [H2O2]:[Fe2+] for photo-Fenton, and independent variable COD reduction. Employing a reduced amount of reagent compared compared to values obtained in the optimization studies for B0, oxidation tests were performed using the both chemical processes for various proportions biodiesel/diesel (B0, B5, B25, B50, B75 and B100). For photo-Fenton process, using the relationship COD:[H2O2]:[Fe2+] = 1:1:0,25, the removal of organic matter in different mixtures diesel/biodiesel was above 80% in terms of COD, except for B0 and B5, which showed maximum removal of 60%. For Fenton process, using the relationship COD:[H2O2]:[Fe2+] = 1:1:0,5, an oxidation was observed between 40 and 50%for fractions containing minor portions of biodiesel (B0 and B5) and greater than 70% for all other mixtures. After treatment by Fenton, the mixtures increased by 150% of biodegradability. The kinetic adjustment of the oxidation reaction by the processes shown that the experimental data can be described by a model in relation to the substrates studied, which takes into account rapid changes in the rate of speed along the reaction. The reaction constant increased as the biodiesel content in the mixture increased. The oxidation processes of the mixtures were best described by a kinetic equation proposed by Chan & Chu (2003).